Do Regulations Based on Credit Ratings Affect a Firm's Cost of Capital? - Kisgen, Darren J.; Strahan, Philip E. (Review of Financial Studies, 2010)
[In February 2003, the U.S. Securities and Exchange Commission officially certified a fourth credit rating agency, Dominion Bond Rating Service (DBRS), for use in bond investment regulations. After DBRS certification, bond yields change in the direction implied by the firm's DBRS rating relative to its ratings from other certified rating agencies. A one-notch-higher DBRS rating corresponds to a 39-basis-point reduction in a firm's debt cost of capital. The impact on yields is driven by cases where the DBRS rating is better than other ratings and is larger among bonds rated near the investment-grade cutoff. These findings indicate that ratings-based regulations on bond investment affect a firm's cost of debt capital.]